Discussion - Paleoplacers Of The Witwatersrand Basin (e94d270f-219f-494a-a532-814aa60a31fa) - W. E. L. Minter (Society for Mining, Metallurgy & Exploration, 1993)
Discussion by R.W. Hutchinson Minter's excellent recent paper (1990) on the great paleoplacer gold deposits of the Witwatersrand and its subsequent discussion (Cheney, 1991) and reply (Minter, 1991) provide an informative, interesting and up-to-date review of the geology of these unique ores and some long enigmatic questions regarding their origin. Clearly summarized by Minter (1990) are the compelling sedimentologic and stratigraphic relationships indicating that the Central Rand Group conglomerates are ancient placers and documenting the fluvio-deltaic conditions of their transport and deposition. As Minter (1991) indicates, Cheney's discussion broadens Minter's 1990 coverage of the subject by considering higher and lower stratigraphic units and by adding detailed comments concerning recently published information about metamorphic and age relationships. Cheney's discussion and Minter's reply also readdress the old controversy of epigenetic hydrothermal vs. syndepositional placer origin for these deposits. This controversy has been resurrected by: • recent recognition of hydrothermally-altered granites (HAGS) in the older Archean basement rocks that lie unconformably beneath the Dominion Group rocks north and west of the Witwatersrand depository; • recognition of greenschist metamorphic assemblages in the Witwatersrand strata; and • the presence of interpreted epigenetic mineral assemblages and textures in some of the deposits. These relationships are briefly discussed by Cheney who suggests they may result from later, superimposed metamorphism and deformation and do not prove that the gold was introduced by epigenetic/metamorphogenic processes. In his paper, Minter (1990) cited the 1986 abstract of a subsequently published paper by Hutchinson and Viljoen (1988) who also considered many of these aspects and attempted to integrate them all in abroad genetic hypothesis. In addition, they emphasized the additional important problem of determining the source for the Witwatersrand gold. Although this issue was partially addressed by Reimer (1984), Mossman and Dyer (1985) and Reimer and Mossman (1990), the question has been generally under emphasized in earlier work and was, therefore, not stressed by Minter and Cheney. Reimer (1985) also emphasized the importance of weathering of the basin's Archean hinterland and its affects on Witwatersrand sedimentation. Since the epigenetic hydrothermal hypothesis was essentially discarded in favor of placerist origin, the gold source for these great deposits has generally been attributed to the weathering of lodes in greenstones or granites of the uplifted, older Archean hinterland to the north and west. However, Hutchinson & Viljoen (1988) present evidence that this explanation is inadequate, as well as data in support of an alternative explanation. They suggest that the gold and accompanying abundant, clearly detrital and auriferous pyrite in the conglomerate reefs were derived by erosional degradation of auriferous-pyritic exhalite previously deposited, by shallow marine discharge of hydrothermal fluids, along the fault-bound northwestern margins of the Witwatersrand depository. The auriferous-pyritic exhalites were generated by fluid-rock reactions in the subsurface, particularly in the highly-altered lavas of the Dominion Group but also in adjacent basement granitic rocks. The process envisaged is comparable to that observed in sea floor hydrothermal systems today, although, in this case, it occurred at the margin of a rapidly subsiding, shallow marine or continental basin. Important evidence for this explanation is the anomalous gold content of the ferruginous, shaley strata occurring throughout the Witwatersrand Supergroup and including the distinctive contorted bed that is an iron formation. These layers have been interpreted (Hutchinson and Viljoen, 1988 and 1990) to represent the more distal, finer-grained, mixed chemical/clastic sedimentary strata. Thus, they are the basinal equivalents of the proximal, auriferous-pyritic exhalites that were deposited along the basin's margin and subsequently reworked by sedimentary processes. This gold source explanation resolves many of the enigmatic questions regarding Witwatersrand geology and the reawakened controversy between proponents of hydrothermal and placerist genetic hypotheses. The theory invokes a hydrothermal origin for the gold in the basin-margin pyritic exhalites, thus explaining the visible hydrothermal characteristics (Figs. 1 and 2). It also provides compelling evidence for placer origin by encompassing all of the fluvio-deltaic processes of clastic sedimentary transport and deposition that are clearly summarized by Minter. These characteristics result from the degradational reworking of the pyritic exhalites along the depository's margins. Fluvial reworking, transport and deltaic redeposition of this detritus, along with additional detritus carried into the depository from the hinterland, then formed the conglomerate reefs. Other enigmatic aspects of Witwatersrand geology include: • the rarity of magnetite and ilmenite (the two most common heavy minerals in placer deposits) and the contrary abundance of leucoxene in the conglomerate reefs; • the presence of differing varieties of pyrite (authigenic, allogenic, compact and porous) all of which are auriferous; and • the presence of well-rounded pebbles, even cobbles, of pyrite that, in view of the brittleness of the mineral, could not have been transported great distances from a hinterland.